Implementation Of Public Health Program Model To Manage Malnutrition Among Under-Five Children In Purworejo District, Central Java - Risnawati, Risnawati; Susilowati, Tuti; Apreliasari, Helmy (Universitas Sari Mulia, 2024)
Background:Purworejo District in Indonesia has a persistent issue of high malnutrition rates among children under five years old. Despite efforts, the prevalence of malnutrition in this demographic continues to rise, highlighting the urgent need for effective health interventions.Aim:This study aimed to develop and evaluate the